Radiological factors that predict the degree of resection and functional preservation in patients with vestibular schwannomas: https://doi.org/10.59156/revista.v37i02.371 - Acevedo Mantilla, Luz Andreina; Villalonga , Juan Francisco; Saenz, Amparo; Baldoncini, Matías; Funes, Tomas; Campero, Alvaro (Revista Argentina de Neurocirugía, 2023)
Introduction: There are various predictors of degree of resection surgery for vestibular schwannomas (SV). Our team in Tucumán carried out a systematic perioperative study with a specific magnetic resonance imaging (MRI) protocol in these patients. The objective of the present study was to determine the usefulness of MRI as a predictor of the degree of resection of VS.Materials and methods: A retrospective and descriptive study of patients operated on for VS was carried out by our team in Tucumán, between January 2014 and December 2020 (n:92). Statistical correlation was made between the imaging characteristics and the degree of resection.Results: A solid tumor increases 39.19 times the probability of having a complete resection compared to a cystic tumor.Conclusion: MRI allows to adequately define tumor consistency; a solid tumor is associated with a higher probability of total resection.
Keywords: vestibular schwannoma; neurofibromatosis; functional outcome